2023
DOI: 10.3390/s23031216
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Algorithm for Insulator Target Detection and Defect Identification

Abstract: The accuracy of insulators and their defect identification by UAVs (unmanned aerial vehicles) in transmission-line inspection needs to be further improved, and the model size of the detection algorithm is significantly reduced to make it more suitable for edge-end deployment. In this paper, the algorithm uses a lightweight GhostNet module to reconstruct the backbone feature extraction network of the YOLOv4 model and employs depthwise separable convolution in the feature fusion layer. The model is lighter on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…On the basis of focal loss, the paper fuses SIOU loss for boundary regression. Defining the fused boundary regression loss function focal-SIOU-loss as follows: LFocal_SIOU=FLγLSIOU,FL(pt)=αt(1pt)γ log(pt),where FL is the focal loss, γ is a super parameter used to control curve radian, αnormalt weight helps to deal with the imbalance of categories, and (1ptfalse)γ is a regulating factor, LSIOU loss function used for boundary regression, compared with CIOU, 31 DIOU, GIOU, 32 and EIOU, 33 SIOU not only considers the length and width information of the prediction box but also considers the matching angle direction. The prediction box returns to the nearest x-axis or y-axis faster.…”
Section: Cn-yolo Network Structurementioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of focal loss, the paper fuses SIOU loss for boundary regression. Defining the fused boundary regression loss function focal-SIOU-loss as follows: LFocal_SIOU=FLγLSIOU,FL(pt)=αt(1pt)γ log(pt),where FL is the focal loss, γ is a super parameter used to control curve radian, αnormalt weight helps to deal with the imbalance of categories, and (1ptfalse)γ is a regulating factor, LSIOU loss function used for boundary regression, compared with CIOU, 31 DIOU, GIOU, 32 and EIOU, 33 SIOU not only considers the length and width information of the prediction box but also considers the matching angle direction. The prediction box returns to the nearest x-axis or y-axis faster.…”
Section: Cn-yolo Network Structurementioning
confidence: 99%
“…where FL is the focal loss, γ is a super parameter used to control curve radian, α t weight helps to deal with the imbalance of categories, and ð1 − p t Þ γ is a regulating factor, L SIOU loss function used for boundary regression, compared with CIOU, 31 DIOU, GIOU, 32 and EIOU, 33 SIOU not only considers the length and width information of the prediction box but also considers the matching angle direction. The prediction box returns to the nearest x-axis or y-axis faster.…”
Section: Focal-siou-loss For Model Convergencementioning
confidence: 99%
“…Unlike a plain network with only a single path of input to output, the residual network is a collection of many paths; therefore, removing certain paths or layers still leaves the other half path valid [ 51 ]. In addition to pruning techniques, in some studies, the backbones of the YOLO models are replaced with lighter convolutional networks, such as EfficientNet [ 52 ], MobileNetv3 [ 53 ], GhostNet [ 54 ] and DenseNet [ 55 ]. Previous research has shown that channel and layer pruning are mainly done to realise more feasible automatic detections.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as a low-cost, short-cycle, and highly maneuverable inspection method, drones are receiving increasing attention in power transmission line inspection [ 8 , 9 , 10 ]. By processing the images of transmission lines obtained through unmanned aerial vehicle (UAV) inspection, it is possible to accurately detect hidden dangers in transmission lines, reduce the incidence of accidents, and improve the reliability of the power grid operating environment [ 11 , 12 , 13 ]. Processing and analyzing images captured by UAVs can effectively detect the positions of electrical components and provide technical support for autonomous inspections of transmission line components using UAVs, the autonomous navigation of UAVs, the automatic focusing of cameras, and defect identification.…”
Section: Introductionmentioning
confidence: 99%